우주잔해물의 적극적 제거에 관한 비판적 고찰 - 김성원(Kim, Sung-Won) (Tonga pŏphak, 2021)
우주활동의 증가에 따라 우주잔해물 문제는 국제사회가 협력하여 해결해야 하는 심각한 문제로 대두되고 있다. 우주잔해물은 국가의 외기권의 자유로운 이용, 탐색 및 접근을 심각하게 제약하며, 외기권 환경의 장기 지속가능성에 심각한 문제를 야기한다. 국제사회는 5개 UN 우주조약의 간접적 적용 및우주잔해물경감지침 및 우주잔해물경감계획을 수립하여 우주잔해물 문제에대응하고 있지만, 그 실효성 측면에서는 큰 효과를 보고 있지 않다. 우주잔해물은 기능중인 우주물체의 파괴를 유발하며, 이러한 파괴를 통해서 새로운 우주잔해물이 생성된다. 우주활동의 증가로 우주잔해물은 더욱 증가할 것으로 쉽게 전망할 수 있는바, 조속히 실효적인 우주잔해물 경감 및 제거를 위한 현실적인 방법이 고안되어야 한다. 이러한 측면에서 우주잔해물의적극적 제거(ADR) 방법은 국제사회가 직면한 우주잔해물 문제의 해결에 있어서 적지 않은 도움이 될 것이다. 그러나, ADR은 우주잔해물의 제거에 도움이 될 수 있지만, 우주잔해물 관련 5개 UN 우주조약의 적용에 관하여 적지 않은 문제를 유발한다. ADR의시행에서 유발되는 문제는 우주활동에 대한 국가들의 경쟁이 심화되는 점을감안할 때, 국가 간의 분쟁의 소지가 될 가능성이 크다. 특히 ASAT 체제로사용될 수 있는 ADR의 이중용도를 감안할 때, 우주잔해물의 경감 및 제거로시작된 ADR의 시행이 우주의 군사화 및 우주의 무기화로 연결될 가능성을배제할 수 없다. 우주잔해물 및 ADR의 시행이 야기하는 문제를 직접 다루는 법적 구속력을 가지는 국제적 합의를 도출하는 것이 상기한 문제를 포괄적으로 해결하는방법이다. 그러나, 우주활동에 국가들이 경쟁적으로 참여함으로써 이와 같은국제적 합의는 쉽게 도출될 것으로 전망되지 않는다. 외기권의 평화적 환경유지 및 우주의 군사화 또는 우주의 무기화 방지라는 두 가지 목적을 모두 충족시킬 수 있는 보다 정교한 ADR 관련 기술의 발전이 안정적으로 제시되지않는 한, 우주잔해물 제거 및 경감 관련 ADR의 시행에서 유발되는 문제는쉽게 해결되지 않을 것이다. 우주과학기술과 우주법의 밀접한 조우(Close Encounters)가 절실히 요구되는 시점이다. With the increase in space activity, the problem of space debris has emerged as a serious concern that the international community must cooperate to solve. Space debris seriously limits States' exploration, use and access of outer space, and poses serious problems for the long-term sustainability of the outer space environment. The international community is responding to the problem of space debris by indirect application of the five UN Treaties concerning outer space and introduction of spade debris mitigation guideline and projects. However, these kinds of the international community's efforts do not yield satisfactory results. Space debris causes the destruction of functioning space objects, and new space debris is created through such destruction. As space debris can easily be predicted to increase further due to the increase in States' space activities, practical solutions for effective space debris reduction and removal must be devised as soon as possible. In this respect, the Active Debris Removal(ADR) will be of considerable help in solving the problem of space debris. However, while ADR can help in the removal of space debris, it raises a number of problems with the application of the five UN treaties with regard to space debris. Problems arising from the ADR are likely to be subject to disputes between States, given the intensifying competition for space activities. In particular, given the dual use of ADR, which can be used as an ASAT system, it cannot be ruled out the possibility that the ADR, which started with the reduction and removal of space debris, will lead to the weaponization and the militarizaiton of outer space. Creating a legally binding international instruments directly addressing space debris and the ADR would be a comprehensive solution to above-mentioned problems. However, it is not expected that such an international legally binding instruments would be easily adopted due to States' competitive participation in space activities. Without the development of more sophisticated ADR-related technologies satisfying requirements of maintaining a peaceful environment of outer space and the attempt to prevent the weaponization and the militarization of outer space, the ADR related to space debris removal and mitigation poses another difficult issues to the international community. The close encounter between space science and technology and international space law (Close Encounters of the Third Kind) is in desperate need. KCI Citation Count: 0